Theorizing digital cultures - Bollmer, Grant (Los Angeles Sage, 2018)
The rapid development of digital technologies continues to have far reaching effects on our daily lives. This book explains how digital media--in providing the material and infrastructure for a host of practices and interactions--affect identities, bodies, social relations, artistic practices, and the environment.--Publisher's description.
Introduction: Why theorize digital cultures? -- Part I: Defining digital cultures: What are digital cultures? -- Culture and technique -- Digital and analogue. -- Part II: Histories, concepts, and debates: Cybernetics and posthumanism -- Identities and performances -- Bodies and extensions -- Aesthetics and affects -- Forms and judgements -- Infrastructures and ecologies. -- Afterword: What comes after digital cultures?
Includes bibliographical references (pages 229-243) and index.
Keywords: Information society -- Social aspects; Information technology -- Social aspects; Digital media -- Social aspects